Ungeneralizable minimality in Ndebele - Laura J. Downing (LibraryPress@UF, 2001)
A body of work in Prosodic Morphology clearly establishes the importance of prosodic constituents like the foot as templates conditioning morpheme size. A striking finding of this research is that morphological footing is independent of metrical footing in many languages, as the footing required for particular morphological processes is often not identical to that required for phonological processes like stress assignment. However, recent OT research on Prosodic Morphology has made the opposite claim. Within this theory, the Generalized Template Hypothesis (GTH) proposes that no morpheme-particular templates defining minimal and maximal size are necessary. Instead, templates are always derivable from general principles of the grammar, like independently motivated metrical footing. This paper presents evidence from Ndebele showing that the GTH is too strong. In Ndebele, several different verb forms are subject to a minimality condition. In some cases, the minimality condition can be derived through independent metrical footing, as the GTH predicts. However, in several cases it cannot, showing that morpheme-particular size constraints are still a necessary part of the grammar.